Enhancement of Aerobic Granulation with -acyl Homoserine Lactone in Treatment Process for Anaerobic Digestion Sidestream - Eunyoung Lee; Kyung Jin Min; Eun Ae Jang; Ki Young Park (대한환경공학회지)
Wastewater treatment plants face challenges in improving nutrient removal efficiency, recovering resources from sludge, and maintaining sustainable processes. This study aims to evaluate the effects of the AHL (N-acyl-homoserine lactone) signaling molecule, C8-HSL, on the formation, stability, and treatment performance of aerobic granular sludge (AGS) in a continuous operation process for side-stream wastewater treatment. Two 2L laboratory-scale continuous reactors were operated for 290 days. The control reactor (A) and the experimental reactor (B) with 5μM of C8-HSL were compared in terms of sludge granule size, extracellular polymeric substances (EPS) composition, chemical oxygen demand (COD), total nitrogen (T-N), total phosphorus (T-P) removal efficiencies, and microbial community changes. The addition of C8-HSL increased the granule size in reactor B by 1.8 times and enhanced TB-EPS and LB-EPS by 1.7 and 2.8 times, respectively. While COD removal efficiencies were similar in both reactors, T-N and T-P removal efficiencies in reactor B increased by 5.2% and 3.8%, respectively. Microbial community analysis revealed an increased abundance of EPS-producing bacteria, such as Thauera, improving sludge cohesion and stability. The addition of AHL signaling molecules significantly enhanced granule size, stability, and nutrient removal performance. This study demonstrates the potential for sustainable wastewater treatment using AHL-mediated quorum sensing technology in AGS processes.